2016
DOI: 10.1155/2016/1870305
|View full text |Cite
|
Sign up to set email alerts
|

Celiac Disease and Gluten-Free Oats: A Canadian Position Based on a Literature Review

Abstract: This paper provides an overview of the latest scientific data related to the safety of uncontaminated oats (<20 ppm of gluten) in the diet of individuals with celiac disease (CD). It updates the previous Health Canada position posted on the Health Canada website in 2007 and a related paper published in 2009. It considers a number of recent studies published between January 2008 and January 2015. While recognizing that a few people with celiac disease seem to be clinically intolerant to oats, this review conclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 41 publications
2
42
0
Order By: Relevance
“…In 2016, a Canadian position paper also concluded that oats uncontaminated by wheat, barley and rye can be safely ingested by most CD patients and that there is no conclusive evidence that the consumption by CD patients of uncontaminated or specially produced oats containing no greater than 20 ppm gluten, should be limited to a specific daily amount. They advise to introduce uncontaminated oats in the gluten-free diet after all symptoms of CD have resolved (La Vieille et al, 2016).…”
Section: Gluten Contamination As Major Cause Of Immunogenicitymentioning
confidence: 99%
“…In 2016, a Canadian position paper also concluded that oats uncontaminated by wheat, barley and rye can be safely ingested by most CD patients and that there is no conclusive evidence that the consumption by CD patients of uncontaminated or specially produced oats containing no greater than 20 ppm gluten, should be limited to a specific daily amount. They advise to introduce uncontaminated oats in the gluten-free diet after all symptoms of CD have resolved (La Vieille et al, 2016).…”
Section: Gluten Contamination As Major Cause Of Immunogenicitymentioning
confidence: 99%
“…In the human intestine, high β‐glucan solubility and high molecular weight (MW) distribution result in increased viscosity, which can delays absorption of glucose and suppresses absorption of cholesterol and reabsorption of bile acids (Anttila et al ., ), that can promotes health benefits, such as improved glycemic response (Zhang et al ., ) and decreased cholesterol level (Wang & Ellis, ). Oat consumption was reported to be of benefit to those suffering from celiac disease (La Vieille et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Gluten-free materials are good sources for people who have celiac disease, a genetically disorder on low tolerance of gluten ingestion. The presence of gluten in celiac people may damage the mucosa of the small intestine and produce a variety of sign and symptoms (La Vieille et al 2016;Adriaanse et al 2016).…”
Section: Introductionmentioning
confidence: 99%